A reflection on analytical tornado-like vortex flow field models. Issue 174 (March 2018) - Gillmeier, S.; Sterling, M.; Hemida, H.; Baker, C.J.
Abstract: Given the difficulties associated with undertaking full-scale measurements in tornadoes, recourse is often made to models. In this field, analytical models have, perhaps surprisingly, stood the test of time, with the Rankine, Burgers-Rott and Sullivan models frequently invoked to model the flow field of a tornado. These mathematical models are by their very nature, a simplification of what is a highly complex phenomenon. However, in many cases they have been represented as the 'truth' without the fundamental assumptions governing the model being either explored in detail or even acknowledged. This paper attempts to rectify this by giving detailed information about assumptions and limitations of each vortex model and critically assesses the ability (or otherwise) of the Rankine, Burgers-Rott, Sullivan, and the recently published Baker vortex model to simulate tornado-like flow. Comparisons are made to the flow field of a physically simulated tornado, which by its very nature is also a model, but arguably more realistic. It was found that the vortex models are able to represent certain flow patterns at certain heights but fail, due to their simplifications, in replicating the entire three-dimensional flow structure obtained experimentally. Highlights: Detailed information about the derivation and simplifications of different vortex models is provided. The performance of these models to simulate tornado flow fields is bench marked against experimentally obtained data. This research area is highly complex, largely due to the interpretation of the different parameters involved. Vortex models are able to represent certain flow patterns but fail in replicating the entire three-dimensional flow structure.